Empirical essays in macroeconomics heterogeneous firms, workers, and industries - Gabriel Züllig (University of Copenhagen, Department of Economics, 2020)
This thesis consists of three self-contained chapters in the area of Macroeconomics. The common thread throughout the studies is the role of heterogeneous and interconnected firms in the economy. The first two chapters use granular data on firms from Denmark to study the adjustment to shocks: In chapter 1, I identify credit constrained firms during the Great Recession and explore the adjustment margin along many dimensions, in particular their workers' wages. The results I find are in line with large swings in employment after financial shocks, and the following low wage growth. In chapter 2, I study how firms adjust prices to changes in cost. For the final analysis, the last chapter assesses whether the presence of interlinkages between firms at the sector level can be used to improve a policymaker's forecast of the aggregate economy.
Keywords: 330